A graphene-based aluminum-based composite heat sink and its preparation process

Through the electrostatic self -assembly technology and thermal treatment process of graphene and aluminum powder, aluminum -based composite heat sinks are prepared, the existing heat dissipation tablets have a large weight and insufficient heat dissipation performance, and the efficient and lightweight heat dissipation effect is achieved.

CN118524672BActive Publication Date: 2025-01-24JIANGSU WEILIAN MASCH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410580876.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2025-01-24
Estimated Expiration
2044-05-11

AI Technical Summary

Technical Problem

The existing heat sink cannot meet the needs of lightweight and efficient heat dissipation in use, and the heat dissipation performance of pure aluminum heat sinks is insufficient.

Method used

The electrostatic self-assembly technology of graphene and aluminum powder is used to prepare aluminum-based composite heat sinks through hot pressing sintering and hot extrusion processes, and grooves are formed on the surface to form heat dissipation grooves, and a reduced graphene oxide film is pasted as a surface heat sink.

Benefits of technology

The thermal conductivity and tensile strength of the heat sink are improved, the heat dissipation effect is enhanced, and the weight is reduced, improving the practicality of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of heat sink technology, specifically to a graphene-based aluminum-based composite heat sink and its preparation process. The solution is to first ball-mill aluminum powder to obtain ball-milled aluminum powder, then surface-treat it with a cationic surfactant to make it positively charged, and then assemble it with negatively charged graphene oxide by electrostatic adsorption, so that the graphene oxide sheet can be evenly adsorbed on the surface of the aluminum powder to form an aluminum-based composite powder, and then hot-press sintering and hot extrusion process are used to obtain a bottom heat sink, and then the reduced graphene oxide film is used as the surface heat sink, and the surface heat sink is adhered to the bottom heat sink by a thermal conductive adhesive to obtain an aluminum-based composite heat sink; compared with conventional pure aluminum heat sinks, the aluminum-based composite heat sink prepared by the present application has a higher heat dissipation effect, is lighter in weight, and is more practical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat sinks, and in particular to a graphene-based aluminum-based composite heat sink and a preparation process thereof. Background Art

[0002] A heat sink is a device that dissipates heat from heat-prone electronic components in electrical appliances. It is usually made of aluminum alloy, brass or bronze in the form of plates, sheets, or multiple sheets. For example, a computer CPU, LED backlight module, etc. require a fairly large heat sink. Generally, a heat sink should be coated with a layer of thermal conductive silicone grease on the contact surface between the electronic component and the heat sink during use, so that the heat generated by the component can be more effectively transferred to the heat sink, and then dissipated to the surrounding air through the heat sink.

[0003] Most of the heat sinks currently available on the market are made of pure aluminum or aluminum alloy, which are of high quality and do not meet the "lightweight" goal of existing research and development. The heat dissipation performance cannot meet actual needs. Therefore, in order to improve the heat dissipation effect of the product, the present invention discloses a graphene-based aluminum-based composite heat sink and its preparation process to solve this technical problem. Summary of the invention

[0004] The object of the present invention is to provide a graphene-based aluminum-based composite heat sink and a preparation process thereof to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A preparation process of a graphene-based aluminum-based composite heat sink comprises the following steps:

[0007] Step (1): mixing nanographite sheets, graphene oxide and magnetic graphene oxide, dissolving them in deionized water, and ultrasonically dispersing them for 1 to 2 hours to form a dispersion, brushing the dispersion onto a polytetrafluoroethylene substrate, and vacuum drying at 60 to 70° C. to obtain a graphene oxide film, and then reducing the film in a hydrazine hydrate solution, washing with deionized water, and drying the film. After drying, the film is transferred to 900 to 950° C. and heat treated for 0.5 to 1 hour to obtain a surface heat sink;

[0008] Step (2): placing aluminum powder in a ball mill, ball milling at 300-400 rpm for 2-4 hours, filtering after ball milling, drying at 60-70° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder;

[0009] The cationic surfactant and distilled water are mixed, stirred at 50-55°C to obtain a surfactant aqueous solution, ball-milled aluminum powder is added to the surfactant aqueous solution, ultrasonically dispersed for 20-30 minutes, stirred for 1-1.5 hours, washed and dried to obtain pretreated aluminum powder;

[0010] The pretreated aluminum powder and distilled water are mixed, ultrasonically dispersed for 40 to 60 minutes, and then the graphene oxide aqueous dispersion is added, stirred for 1 to 2 hours, and filtered to obtain an aluminum-based composite powder;

[0011] Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, cooling it and then heating it to 450-480°C at a heating rate of 10°C / min, keeping it warm for 30-40min, taking it out and hot extruding it at a pressure of 640-650MPa, keeping the pressure for 5-8s, demolding and cooling it to obtain a bottom heat sink;

[0012] Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

[0013] In a more optimized solution, in step (1), the concentration of the dispersion is 60-70 mg / mL, the concentration of the hydrazine hydrate solution is 20-30 mg / mL; and the mass ratio of the nanographite sheets, graphene oxide, and magnetic graphene oxide is 1:(3-4):1.

[0014] In a more optimized solution, in step (2), alumina grinding balls are used for ball milling, the ball-to-material mass ratio is (3-4):1, the solvent is anhydrous ethanol; the cationic surfactant is hexadecyltrimethylammonium bromide, and the mass concentration of the surfactant aqueous solution is 1-2%; the amount of graphene oxide used is 0.5-1wt% of the pretreated aluminum powder.

[0015] In a more optimized solution, in step (3), the total area of ​​the heat sink is A, and the single-side area of ​​the bottom heat sink is B, then 50%B≤A≤85%B.

[0016] For a more optimized solution, the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, and the coating thickness of the thermal conductive adhesive is M2. Then 1 / 3N≤M≤2 / 3N, 70%M<M1+M2<90%M.

[0017] In a more optimized solution, in step (1), during vacuum drying, the total drying time is H. First, the polytetrafluoroethylene substrate is placed horizontally and placed in a horizontal magnetic field, with the direction of the magnetic field parallel to the polytetrafluoroethylene substrate. Dry for 0.1H, then the polytetrafluoroethylene substrate is placed vertically, with the direction of the magnetic field perpendicular to the polytetrafluoroethylene substrate. Dry for 0.2H, and alternately adjust the position of the polytetrafluoroethylene substrate until the total drying time reaches H to form a graphene oxide film.

[0018] In a more optimized solution, in step (1), the preparation steps of magnetic graphene oxide are:

[0019] Take ferric chloride hexahydrate and distilled water, mix them, stir until they are completely dissolved, then add boiling distilled water, boil for 2 to 3 minutes, and cool to obtain iron hydroxide colloid; slowly add the iron hydroxide colloid to the graphene oxide aqueous dispersion, let it stand for 20 to 24 hours, collect the product after stratification, wash it and vacuum dry it, then calcine it in a nitrogen environment for 2 to 3 hours, the calcination temperature is 1000 to 1050°C, grind it and pass it through a 100-mesh sieve to obtain magnetic graphene oxide.

[0020] In a more optimized solution, the mass ratio of ferric chloride hexahydrate to graphene oxide is (25-35):1.

[0021] A more optimized solution is an aluminum-based composite heat sink prepared according to any of the preparation processes described above.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The invention discloses an aluminum-based composite heat sink based on graphene and a preparation process thereof. The scheme comprises the following steps: firstly ball-milling aluminum powder to obtain ball-milled aluminum powder, then surface-treating the ball-milled aluminum powder with a cationic surfactant to make it have a positive charge, then assembling the ball-milled aluminum powder with a negatively charged graphene oxide with electrostatic adsorption, so that the graphene oxide sheets can be uniformly adsorbed on the surface of the aluminum powder to form an aluminum-based composite powder, and then hot-pressing and sintering are performed to obtain a bottom heat sink with a hot extrusion process, and then using a reduced graphene oxide film as a surface heat sink, the surface heat sink is adhered to the bottom heat sink with a thermal conductive adhesive to obtain an aluminum-based composite heat sink; compared with conventional pure aluminum heat sinks, the aluminum-based composite heat sink prepared by the present application has a higher heat dissipation effect, is lighter in weight, and is more practical.

[0024] In this solution, the main technical points of this application are:

[0025] (1) The bottom heat sink is formed by electrostatic self-assembly of graphene oxide and aluminum powder, hot pressing and sintering, and then hot extrusion. Compared with the conventional pure aluminum heat sink, its thermal conductivity, tensile strength and other mechanical properties are improved due to the doping of graphene oxide.

[0026] (2) The scheme is to mix nanographite sheets, graphene oxide and magnetic graphene oxide, brush them onto a polytetrafluoroethylene substrate, dry them to prepare a graphene oxide film, and then reduce them with a hydrazine hydrate solution and heat treat them at a high temperature to further form a reduced graphene oxide film, which is used as a surface heat sink. The scheme is doped with magnetic graphene oxide and the drying environment is limited. The specific parameters are "first place the polytetrafluoroethylene substrate horizontally and in a horizontal magnetic field, with the magnetic field direction parallel to the polytetrafluoroethylene substrate, dry for 0.1 hours, and then place the polytetrafluoroethylene substrate vertically, with the magnetic field direction parallel to the polytetrafluoroethylene substrate" Vertically, dry for 0.2H, alternately adjust the position of the polytetrafluoroethylene substrate until the total drying time reaches H, and form a graphene oxide film"; if the total drying time is H, divide it into 10 equal parts, of which the magnetic field environment parallel to the polytetrafluoroethylene substrate is 1 equal part each time, that is, 0.1H, and the magnetic field environment perpendicular to the polytetrafluoroethylene substrate is 2 equal parts each time, that is, 0.2H, and they are arranged alternately in sequence, so that part of the magnetic graphene oxide can be oriented in the longitudinal direction, which can improve the longitudinal thermal conductivity of the reduced graphene oxide film, thereby comprehensively improving the heat dissipation effect of the aluminum-based heat sink.

[0027] (3) When improving conventional heat sinks, it is generally considered to stick graphene heat sinks on both sides of the aluminum substrate. However, when this structure is actually used, the wear rate of the graphene heat sinks on both sides is relatively high. Therefore, the scheme improves the overall structure of the aluminum-based heat sink. After the bottom heat sink is prepared, the surface is grooved to form a plurality of heat sinks, and it is defined that "the plurality of heat sinks are interconnected". At the same time, the area of ​​the heat sink is limited to "the total area of ​​the heat sink is A, and the area of ​​one side of the bottom heat sink is B, then 50% B≤A≤85% B". The purpose is to ensure that the heat sinks are interconnected and the area of ​​the surface heat sink is guaranteed, which can greatly ensure the heat dissipation effect and avoid the reduction of the heat dissipation effect due to this design; on the other hand, the surface heat sink is placed in the heat sink, and the existence of the heat sink can protect it to reduce the loss of the surface heat sink; in addition, the scheme only limits the total area of ​​the heat sink, but does not need to limit the shape of the heat sink, so the heat sink can be designed as a brand logo, petals or other irregular and beautiful graphics according to customer needs.

[0028] At the same time, the plan also limits the thickness of the surface heat sink, specifically "the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, and the coating thickness of the thermal conductive adhesive is M2, then 1 / 3N≤M≤2 / 3N, 70%M<M1+M2<90%M". The depth of the heat sink should not be too deep, otherwise the actual processing difficulty will increase, and the comprehensive mechanical properties of the product cannot be guaranteed. The depth of the heat sink must be greater than the total thickness of the surface heat sink and the thermal conductive adhesive to ensure that the heat sink protects the surface heat sink. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In this embodiment, the preparation steps of nanographite sheets are as follows: placing expanded graphite in anhydrous ethanol, adjusting the pH to 10, and ultrasonically dispersing for 2 hours to obtain nanographite sheets. The graphene oxide model is XFSG01, provided by Xianfeng Nano; the aluminum powder is pure aluminum powder; and the thermal conductive adhesive is 3M5590H.

[0031] Embodiment 1: A preparation process of a graphene-based aluminum-based composite heat sink, comprising the following steps:

[0032] Step (1): The preparation steps of magnetic graphene oxide are:

[0033] Take 8g of ferric chloride hexahydrate and mix it with 50mL of distilled water, stir until it is completely dissolved, then add 200mL of boiling distilled water, the addition time is 30min, boil for 2min, cool to obtain iron hydroxide colloid; dissolve 260mg of graphene oxide powder in distilled water, stir evenly, and ultrasonically disperse for 50min to obtain a graphene oxide aqueous dispersion with a concentration of 0.5mg / mL; then slowly add the iron hydroxide colloid to the graphene oxide aqueous dispersion, the addition time is 30min, let it stand for 24h, collect the product after stratification, wash and vacuum dry, and then calcine under nitrogen environment for 2h, the calcination temperature is 1050℃, grind and pass through a 100-mesh sieve to obtain magnetic graphene oxide.

[0034] Nanographite sheets, graphene oxide and magnetic graphene oxide are mixed, dissolved in deionized water, and ultrasonically dispersed for 1 hour to form a dispersion with a concentration of 60 mg / mL. The dispersion is brushed onto a polytetrafluoroethylene substrate, and vacuum dried at 70°C to obtain a graphene oxide film, which is then reduced in a hydrazine hydrate solution, washed with deionized water, and dried. After drying, the mixture is transferred to 950°C and heat treated for 0.5 hours to obtain a surface heat sink. The concentration of the hydrazine hydrate solution is 25 mg / mL. The mass ratio of the nanographite sheets, graphene oxide and magnetic graphene oxide is 1:4:1.

[0035] During vacuum drying, the total drying time is H. First, the polytetrafluoroethylene substrate is placed horizontally and placed in a horizontal magnetic field with the direction of the magnetic field parallel to the polytetrafluoroethylene substrate. Dry for 0.1H. Then, the polytetrafluoroethylene substrate is placed vertically with the direction of the magnetic field perpendicular to the polytetrafluoroethylene substrate. Dry for 0.2H. The position of the polytetrafluoroethylene substrate is adjusted alternately until the total drying time reaches H to form a graphene oxide film.

[0036] Step (2): placing aluminum powder in a ball mill, ball milling at 300 rpm for 3 h, filtering after ball milling, drying at 60° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder; alumina grinding balls are used during ball milling, the ball-to-material mass ratio is 4:1, and the solvent is anhydrous ethanol.

[0037] The cationic surfactant and distilled water are mixed, stirred evenly at 50°C to obtain a surfactant aqueous solution, 10 g of ball-milled aluminum powder is added to 100 mL of the surfactant aqueous solution, ultrasonically dispersed for 200 min, stirred for 1 h, washed and dried to obtain pretreated aluminum powder; the mass concentration of the surfactant aqueous solution is 1.5%; the cationic surfactant is hexadecyltrimethylammonium bromide.

[0038] The pretreated aluminum powder and distilled water were mixed, ultrasonically dispersed for 40 minutes, and then a 0.5 mg / mL graphene oxide aqueous dispersion was added, stirred for 1 hour, and filtered to obtain an aluminum-based composite powder; the amount of graphene oxide used was 0.5 wt% of the pretreated aluminum powder.

[0039] Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, the sintering pressure is 30MPa, the time is 30min, and after cooling, the temperature is increased to 450°C at a heating rate of 10°C / min, and the temperature is kept for 30min. After taking it out, hot extrusion is performed at a pressure of 650MPa, the pressure is maintained for 5s, and demolding and cooling are performed to obtain the bottom heat sink.

[0040] Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

[0041] The total area of ​​the heat sink is A, the area of ​​one side of the bottom heat sink is B, then A = 75% B; the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, the coating thickness of the thermal conductive adhesive is M2, then M = 1 / 2N; M1 + M2 = 80% M. The thickness of the bottom heat sink is 1mm.

[0042] Embodiment 2: A process for preparing a graphene-based aluminum-based composite heat sink comprises the following steps:

[0043] Step (1): The preparation steps of magnetic graphene oxide are:

[0044] Take 8g of ferric chloride hexahydrate and mix it with 50mL of distilled water, stir until it is completely dissolved, then add 200mL of boiling distilled water, the addition time is 30min, boil for 3min, cool to obtain iron hydroxide colloid; dissolve 260mg of graphene oxide powder in distilled water, stir evenly, ultrasonically disperse for 55min, and obtain a graphene oxide aqueous dispersion with a concentration of 0.5mg / mL; then slowly add the iron hydroxide colloid to the graphene oxide aqueous dispersion, the addition time is 30min, let stand for 22h, collect the product after stratification, wash and vacuum dry, and then calcine for 2.5h in a nitrogen environment, the calcination temperature is 1050℃, and pass through a 100-mesh sieve after grinding to obtain magnetic graphene oxide.

[0045] Nanographite sheets, graphene oxide and magnetic graphene oxide are mixed, dissolved in deionized water, and ultrasonically dispersed for 1.5 hours to form a dispersion with a concentration of 60 mg / mL. The dispersion is brushed onto a polytetrafluoroethylene substrate, and vacuum dried at 70°C to obtain a graphene oxide film, which is then reduced in a hydrazine hydrate solution, washed with deionized water, and dried. After drying, the mixture is transferred to 950°C and heat treated for 0.5 hours to obtain a surface heat sink. The concentration of the hydrazine hydrate solution is 25 mg / mL. The mass ratio of the nanographite sheets, graphene oxide and magnetic graphene oxide is 1:4:1.

[0046] During vacuum drying, the total drying time is H. First, the polytetrafluoroethylene substrate is placed horizontally and placed in a horizontal magnetic field with the direction of the magnetic field parallel to the polytetrafluoroethylene substrate. Dry for 0.1H. Then, the polytetrafluoroethylene substrate is placed vertically with the direction of the magnetic field perpendicular to the polytetrafluoroethylene substrate. Dry for 0.2H. The position of the polytetrafluoroethylene substrate is adjusted alternately until the total drying time reaches H to form a graphene oxide film.

[0047] Step (2): placing aluminum powder in a ball mill, ball milling at 300 rpm for 3 h, filtering after ball milling, drying at 65° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder; alumina grinding balls are used during ball milling, the ball-to-material mass ratio is 4:1, and the solvent is anhydrous ethanol.

[0048] The cationic surfactant and distilled water are mixed, stirred evenly at 55°C to obtain a surfactant aqueous solution, 10 g of ball-milled aluminum powder is added to 100 mL of the surfactant aqueous solution, ultrasonically dispersed for 25 min, stirred for 1.5 h, washed and dried to obtain pretreated aluminum powder; the mass concentration of the surfactant aqueous solution is 1.5%; the cationic surfactant is hexadecyltrimethylammonium bromide.

[0049] The pretreated aluminum powder and distilled water were mixed, ultrasonically dispersed for 50 minutes, and then a 0.5 mg / mL graphene oxide aqueous dispersion was added, stirred for 1.5 hours, and filtered to obtain an aluminum-based composite powder; the amount of graphene oxide used was 0.5 wt% of the pretreated aluminum powder.

[0050] Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, the sintering pressure is 30MPa, the time is 30min, and after cooling, the temperature is increased to 450°C at a heating rate of 10°C / min, and the temperature is kept for 30min. After taking it out, hot extrusion is performed at a pressure of 650MPa, the pressure is maintained for 5s, and demolding and cooling are performed to obtain the bottom heat sink.

[0051] Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

[0052] The total area of ​​the heat sink is A, the area of ​​one side of the bottom heat sink is B, then A = 75% B; the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, the coating thickness of the thermal conductive adhesive is M2, then M = 1 / 2N; M1 + M2 = 80% M. The thickness of the bottom heat sink is 1mm.

[0053] Embodiment 3: A process for preparing a graphene-based aluminum-based composite heat sink comprises the following steps:

[0054] Step (1): The preparation steps of magnetic graphene oxide are:

[0055] Take 8g of ferric chloride hexahydrate and mix it with 50mL of distilled water, stir until it is completely dissolved, then add 200mL of boiling distilled water, the addition time is 30min, boil for 3min, cool to obtain iron hydroxide colloid; dissolve 260mg of graphene oxide powder in distilled water, stir evenly, and ultrasonically disperse for 60min to obtain a graphene oxide aqueous dispersion with a concentration of 0.5mg / mL; then slowly add the iron hydroxide colloid to the graphene oxide aqueous dispersion, the addition time is 30min, let it stand for 24h, collect the product after stratification, wash and vacuum dry, and then calcine under nitrogen environment for 3h, the calcination temperature is 1050℃, grind and pass through a 100-mesh sieve to obtain magnetic graphene oxide.

[0056] Nanographite sheets, graphene oxide and magnetic graphene oxide are mixed, dissolved in deionized water, and ultrasonically dispersed for 2 hours to form a dispersion with a concentration of 60 mg / mL. The dispersion is brushed onto a polytetrafluoroethylene substrate, and vacuum dried at 70°C to obtain a graphene oxide film, which is then reduced in a hydrazine hydrate solution, washed with deionized water, and dried. After drying, the mixture is transferred to 950°C and heat treated for 0.5 hours to obtain a surface heat sink. The concentration of the hydrazine hydrate solution is 25 mg / mL. The mass ratio of the nanographite sheets, graphene oxide and magnetic graphene oxide is 1:4:1.

[0057] During vacuum drying, the total drying time is H. First, the polytetrafluoroethylene substrate is placed horizontally and placed in a horizontal magnetic field with the direction of the magnetic field parallel to the polytetrafluoroethylene substrate. Dry for 0.1H. Then, the polytetrafluoroethylene substrate is placed vertically with the direction of the magnetic field perpendicular to the polytetrafluoroethylene substrate. Dry for 0.2H. The position of the polytetrafluoroethylene substrate is adjusted alternately until the total drying time reaches H to form a graphene oxide film.

[0058] Step (2): placing aluminum powder in a ball mill, ball milling at 300 rpm for 3 h, filtering after ball milling, drying at 70° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder; alumina grinding balls are used during ball milling, the ball-to-material mass ratio is 4:1, and the solvent is anhydrous ethanol.

[0059] The cationic surfactant and distilled water are mixed, stirred evenly at 55°C to obtain a surfactant aqueous solution, 10 g of ball-milled aluminum powder is added to 100 mL of the surfactant aqueous solution, ultrasonically dispersed for 30 min, stirred for 1.5 h, washed and dried to obtain pretreated aluminum powder; the mass concentration of the surfactant aqueous solution is 1.5%; the cationic surfactant is hexadecyltrimethylammonium bromide.

[0060] The pretreated aluminum powder and distilled water were mixed, ultrasonically dispersed for 60 minutes, and then a 0.5 mg / mL graphene oxide aqueous dispersion was added, stirred for 2 hours, and filtered to obtain an aluminum-based composite powder; the amount of graphene oxide used was 0.5 wt% of the pretreated aluminum powder.

[0061] Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, the sintering pressure is 30MPa, the time is 30min, and after cooling, the temperature is increased to 450°C at a heating rate of 10°C / min, and the temperature is kept for 30min. After taking it out, hot extrusion is performed at a pressure of 650MPa, the pressure is maintained for 5s, and demolding and cooling are performed to obtain the bottom heat sink.

[0062] Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

[0063] The total area of ​​the heat sink is A, the area of ​​one side of the bottom heat sink is B, then A = 75% B; the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, the coating thickness of the thermal conductive adhesive is M2, then M = 1 / 2N; M1 + M2 = 80% M. The thickness of the bottom heat sink is 1mm.

[0064] Comparative Example 1: A preparation process of a graphene-based aluminum-based composite heat sink, comprising the following steps:

[0065] Step (1): Mix nanographite sheets and graphene oxide, dissolve them in deionized water, and ultrasonically disperse them for 2 hours to form a dispersion with a concentration of 60 mg / mL. Apply the dispersion to a polytetrafluoroethylene substrate, and vacuum dry it at 70°C to obtain a graphene oxide film. Then, place it in a hydrazine hydrate solution for reduction, wash it with deionized water, and dry it. After drying, transfer it to 950°C and heat treat it for 0.5 hours to obtain a surface heat sink. The concentration of the hydrazine hydrate solution is 25 mg / mL. The mass ratio of the nanographite sheets to the graphene oxide is 1:4.

[0066] Step (2): placing aluminum powder in a ball mill, ball milling at 300 rpm for 3 h, filtering after ball milling, drying at 70° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder; alumina grinding balls are used during ball milling, the ball-to-material mass ratio is 4:1, and the solvent is anhydrous ethanol.

[0067] The cationic surfactant and distilled water are mixed, stirred evenly at 55°C to obtain a surfactant aqueous solution, 10 g of ball-milled aluminum powder is added to 100 mL of the surfactant aqueous solution, ultrasonically dispersed for 30 min, stirred for 1.5 h, washed and dried to obtain pretreated aluminum powder; the mass concentration of the surfactant aqueous solution is 1.5%; the cationic surfactant is hexadecyltrimethylammonium bromide.

[0068] The pretreated aluminum powder and distilled water were mixed, ultrasonically dispersed for 60 minutes, and then a 0.5 mg / mL graphene oxide aqueous dispersion was added, stirred for 2 hours, and filtered to obtain an aluminum-based composite powder; the amount of graphene oxide used was 0.5 wt% of the pretreated aluminum powder.

[0069] Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, the sintering pressure is 30MPa, the time is 30min, and after cooling, the temperature is increased to 450°C at a heating rate of 10°C / min, and the temperature is kept for 30min. After taking it out, hot extrusion is performed at a pressure of 650MPa, the pressure is maintained for 5s, and demolding and cooling are performed to obtain the bottom heat sink.

[0070] Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

[0071] The total area of ​​the heat sink is A, the area of ​​one side of the bottom heat sink is B, then A = 75% B; the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, the coating thickness of the thermal conductive adhesive is M2, then M = 1 / 2N; M1 + M2 = 80% M. The thickness of the bottom heat sink is 1mm.

[0072] Comparative Example 1 is the control group of Example 3. In Comparative Example 2, magnetic graphene oxide is not doped, and the other processes remain unchanged.

[0073] Comparative Example 2: A preparation process of a graphene-based aluminum-based composite heat sink, comprising the following steps:

[0074] Step (1): The preparation steps of magnetic graphene oxide are:

[0075] Take 8g of ferric chloride hexahydrate and mix it with 50mL of distilled water, stir until it is completely dissolved, then add 200mL of boiling distilled water, the addition time is 30min, boil for 3min, cool to obtain iron hydroxide colloid; dissolve 260mg of graphene oxide powder in distilled water, stir evenly, and ultrasonically disperse for 60min to obtain a graphene oxide aqueous dispersion with a concentration of 0.5mg / mL; then slowly add the iron hydroxide colloid to the graphene oxide aqueous dispersion, the addition time is 30min, let it stand for 24h, collect the product after stratification, wash and vacuum dry, and then calcine under nitrogen environment for 3h, the calcination temperature is 1050℃, grind and pass through a 100-mesh sieve to obtain magnetic graphene oxide.

[0076] Nanographite sheets, graphene oxide and magnetic graphene oxide are mixed, dissolved in deionized water, and ultrasonically dispersed for 2 hours to form a dispersion with a concentration of 60 mg / mL. The dispersion is brushed onto a polytetrafluoroethylene substrate, and vacuum dried at 70°C to obtain a graphene oxide film, which is then reduced in a hydrazine hydrate solution, washed with deionized water, and dried. After drying, the mixture is transferred to 950°C and heat treated for 0.5 hours to obtain a surface heat sink. The concentration of the hydrazine hydrate solution is 25 mg / mL. The mass ratio of the nanographite sheets, graphene oxide and magnetic graphene oxide is 1:4:1.

[0077] During vacuum drying, the total drying time is H, the polytetrafluoroethylene substrate is placed horizontally and placed in a horizontal magnetic field, and the direction of the magnetic field is parallel to the polytetrafluoroethylene substrate. When the total drying time reaches H, a graphene oxide film is formed.

[0078] Step (2): placing aluminum powder in a ball mill, ball milling at 300 rpm for 3 h, filtering after ball milling, drying at 70° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder; alumina grinding balls are used during ball milling, the ball-to-material mass ratio is 4:1, and the solvent is anhydrous ethanol.

[0079] The cationic surfactant and distilled water are mixed, stirred evenly at 55°C to obtain a surfactant aqueous solution, 10 g of ball-milled aluminum powder is added to 100 mL of the surfactant aqueous solution, ultrasonically dispersed for 30 min, stirred for 1.5 h, washed and dried to obtain pretreated aluminum powder; the mass concentration of the surfactant aqueous solution is 1.5%; the cationic surfactant is hexadecyltrimethylammonium bromide.

[0080] The pretreated aluminum powder and distilled water were mixed, ultrasonically dispersed for 60 minutes, and then a 0.5 mg / mL graphene oxide aqueous dispersion was added, stirred for 2 hours, and filtered to obtain an aluminum-based composite powder; the amount of graphene oxide used was 0.5 wt% of the pretreated aluminum powder.

[0081] Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, the sintering pressure is 30MPa, the time is 30min, and after cooling, the temperature is increased to 450°C at a heating rate of 10°C / min, and the temperature is kept for 30min. After taking it out, hot extrusion is performed at a pressure of 650MPa, the pressure is maintained for 5s, and demolding and cooling are performed to obtain the bottom heat sink.

[0082] Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

[0083] The total area of ​​the heat sink is A, the area of ​​one side of the bottom heat sink is B, then A = 75% B; the thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, the coating thickness of the thermal conductive adhesive is M2, then M = 1 / 2N; M1 + M2 = 80% M. The thickness of the bottom heat sink is 1mm.

[0084] Comparative Example 2 is the control group of Example 3, in which the magnetic limitation is adjusted in Comparative Example 1, and the other processes remain unchanged.

[0085] Detection experiment:

[0086] 1. Take the bottom heat sink prepared in Example 3 as the sample of Example 3, and take pure aluminum as the control sample, grind and polish the surface of the test sample and the control sample, and test the thermal conductivity of each sample; the original sheet with a thickness of 2mm and a diameter of 12mm is used for the test. Test the tensile strength of each sample at a speed of 1mm / min, and the sample is a dumbbell-shaped specimen. Take the surface heat sink prepared in Example 3 and the surface heat sink prepared in Comparative Examples 1 to 2, and test their transverse thermal conductivity. The specific data are shown in Table 1.

[0087] Table 1

[0088] project Thermal conductivity of bottom heat sink W / (mK) tensile strength Surface heat sink thermal conductivity W / (mK) Example 3 Sample 203.7 246MPa 1127.2 Control samples 164.1 201MPa / Comparative Example 1 Sample / / 1045.3 Comparative Example 2 Sample / / 1086.4

[0089] 2. The aluminum-based composite heat sink prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was adhered to the surface of a silicon wafer, and then the silicon wafer was placed in a 120°C oven for heating for 20 minutes, taken out and allowed to stand at room temperature for 2 minutes, the surface temperature of the silicon wafer was tested, and the temperature difference was recorded. Specific data are shown in Table 2.

[0090] Table 2

[0091] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Temperature difference -37℃ -39℃ -42℃ -33℃ -36℃

[0092] Conclusion: The present invention discloses a graphene-based aluminum-based composite heat sink and a preparation process thereof. Compared with conventional pure aluminum heat sinks, the aluminum-based composite heat sink prepared in the present application has a higher heat dissipation effect, is lighter in weight, and is more practical.

[0093] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation process of a graphene-based aluminum-based composite heat sink, characterized in that: The following steps are involved: Step (1): mixing nanographite sheets, graphene oxide and magnetic graphene oxide, dissolving them in deionized water, and ultrasonically dispersing them for 1 to 2 hours to form a dispersion, brushing the dispersion onto a polytetrafluoroethylene substrate, and vacuum drying at 70° C. to obtain a graphene oxide film, and then reducing the dispersion in a hydrazine hydrate solution, washing with deionized water, and drying the film. After drying, the film is transferred to 950° C. and heat treated for 0.5 hours to obtain a surface heat sink; the concentration of the hydrazine hydrate solution is 25 mg / mL; the concentration of the dispersion is 60 mg / mL; the mass ratio of the nanographite sheets, graphene oxide and magnetic graphene oxide is 1:4:1; Step (2): placing aluminum powder in a ball mill, ball milling at 300 rpm for 3 h, filtering after ball milling, drying at 60-70° C., and passing through a 400-mesh sieve to obtain ball-milled aluminum powder; The cationic surfactant and distilled water are mixed, stirred at 50°C or 55°C to obtain a surfactant aqueous solution, 10g of ball-milled aluminum powder is added to 100mL of the surfactant aqueous solution, ultrasonically dispersed for 20 to 30min, stirred for 1h or 1.5h, washed and dried to obtain pretreated aluminum powder; The pretreated aluminum powder and distilled water are mixed, ultrasonically dispersed for 40 to 60 minutes, and then the graphene oxide aqueous dispersion is added, stirred for 1 to 2 hours, and filtered to obtain an aluminum-based composite powder; the concentration of the graphene oxide aqueous dispersion is 0.5 mg / mL, and the amount of graphene oxide is 0.5 wt% of the pretreated aluminum powder; Step (3): putting the aluminum-based composite powder into a steel casting mold, then placing it in a muffle furnace, heating it to 750°C, hot pressing and sintering, cooling it and then heating it to 450°C at a heating rate of 10°C / min, keeping it warm for 30 minutes, taking it out and hot extruding it at a pressure of 650 MPa, keeping the pressure for 5 seconds, demolding and cooling it to obtain a bottom heat sink; Grooves are made on the surface of the bottom heat sink to form a plurality of heat sinks, which are interconnected. Thermal conductive adhesive is applied to the heat sink, and the surface heat sink is pasted into the heat sink, dried and cured to obtain an aluminum-based composite heat sink.

2. The preparation process of a graphene-based aluminum-based composite heat sink according to claim 1, characterized in that: In step (2), alumina grinding balls are used for ball milling, the ball-to-material mass ratio is 4:1, the solvent is anhydrous ethanol; the cationic surfactant is hexadecyltrimethylammonium bromide, and the mass concentration of the surfactant aqueous solution is 1.5%.

3. The preparation process of a graphene-based aluminum-based composite heat sink according to claim 1, characterized in that: In step (3), the total area of ​​the heat sink is A, and the single-side area of ​​the bottom heat sink is B, then A=75%B.

4. The preparation process of a graphene-based aluminum-based composite heat sink according to claim 1, characterized in that: The thickness of the bottom heat sink is N, the depth of the heat sink is M, the thickness of the surface heat sink is M1, and the coating thickness of the thermal conductive adhesive is M2, then M=1 / 2N, M1+M2=80%M.

5. The preparation process of a graphene-based aluminum-based composite heat sink according to claim 1, characterized in that: In step (1), during vacuum drying, the total drying time is H. First, the polytetrafluoroethylene substrate is placed horizontally and placed in a horizontal magnetic field, with the direction of the magnetic field parallel to the polytetrafluoroethylene substrate. Dry for 0.1H, then the polytetrafluoroethylene substrate is placed vertically, with the direction of the magnetic field perpendicular to the polytetrafluoroethylene substrate. Dry for 0.2H, and alternately adjust the position of the polytetrafluoroethylene substrate until the total drying time reaches H to form a graphene oxide film.

6. An aluminum-based composite heat sink prepared according to the preparation process according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Graphene nanosheet / aluminum composite and preparation method thereof

    CN110578076A

  • Graphene / silicon carbide reinforced copper-based composite material and preparation method thereof

    CN111057899A